INFLUENCE OF NUCLEAR FACTOR κB INHIBITOR ON BIOCHEMICAL MARKERS OF INSULIN RESISTANCE SYNDROME UNDER HYPOPINEALISM AND HIGH-CALORIE CARBOHYDRATE-LIPID DIET - Belikova, O.I.; Frenkel, Yu.D.; Cherno, V.S.; Kostenko, V.O. (World of Medicine and Biology, 2017)
The aim of the work is to clarify the effect of the nuclear factor κB (NF-κB) inhibitor on the biochemical markers of the insulin resistance syndrome under hypopnealism induced by the exposure to round-the-clock light, and the maintenance of high-calorie carbohydrate-lipid (HCHL) diet.Material and methods. The research was conducted on 21 white rats of the Wistar line weighing 215-255 g in 3 series of experiments: the first series was designed to obtain necessary indices in intact animals (control series), in the second series we measured the same indices in the rats subject to modeled syndrome of IR (HCHL diet for 60 days and round-the-clock light with intensity of 1500 lux for the last 30 days of the experiment); in the third series we assessed the indices under administration of ammonium pyrrolidinedithiocarbamate (PDTC - ammonium pyrrolidinedithiocarbamate) in a dose of 76 mg/kg 3 times a week starting on the 30th day of the experiment.The concentration of melatonin, insulin and tumor necrosis factor-α (TNF-α) by enzyme-linked immunosorbent assay, glucose, total cholesterol (CHL), triacylglycerol (TAG), and high-density lipoprotein cholesterol (CHL-HDL), ceruloplasmin, were determined. We calculated the content of low and very low density lipoprotein cholesterol (CHL-LDL and CHL-VLDL) by the Friedwald formula, Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Results. Round-the-clock lightening of the with an intensity of 1500 lux during the period of maintaining the carbohydrate-lipid diet reduces the content of melatonin in the blood serum by 77.7% (p
Keywords: insulin resistance syndrome; hypopinealism; nuclear factor κB; carbohydrate and lipid metabolism; systemic inflammatory response